Involvement of innate immunity in the development of inflammatory and autoimmune diseases. - Tlaskalová-Hogenová, H; Tucková, L; Stepánková, R; Hudcovic, T; Palová-Jelínková, L; Kozáková, H; Rossmann, P; Sanchez, D; Cinová, J; Hrncír, T; Kverka, M; Frolová, L; et al. (2005)
Initial events and effector mechanisms of most inflammatory and autoimmune diseases remain largely unknown. Dysfunction of the innate and adaptive immune systems associated with mucosae (the major interface between the organism and its environment, e.g., microbiota, food) can conceivably cause impairment of mucosal barrier function and development of localized or systemic inflammatory and autoimmune processes. Animal models help in elucidating the etiology and pathogenetic mechanisms of human diseases, such as the inflammatory bowel diseases, Crohn's disease and ulcerative colitis, severe chronic diseases affecting the gut. To study the role of innate immunity and gut microbiota in intestinal inflammation, colitis was induced by dextran sulfate sodium (DSS) in mice with severe combined immunodeficiency (SCID). Conventionally reared (microflora-colonized) SCID mice displayed severe inflammation like that seen in immunocompetent Balb/c mice, whereas only minor changes appeared in the intestinal mucosa of DSS-fed gnotobiotic germ-free SCID mice. The presence of microflora facilitates the inflammation in DSS-induced colitis that develops in immunodeficient SCID mice, that is, in the absence of T and B lymphocytes. Celiac disease, a chronic autoimmune small bowel disorder, afflicts genetically susceptible individuals with wheat gluten intolerance. We showed that, in contrast with any other food proteins, wheat gliadin and its peptic fragments activate mouse macrophages and human monocytes to produce proinflammatory cytokines through the nuclear factor-kappaB signaling pathway. Activation of innate immunity cells by food proteins or components from gut microbiota thus could participate in the impairment of intestinal mucosa and the development of intestinal and/or systemic inflammation.